Implementation of spectral x-ray technique for the identification of different tissues in medical imaging (2018)
The spectral x-ray technique has begun to generate interest in medical imaging because it uses the energetic dependence of the attenuation properties to improve the contrast of images of different materials, and even decrease the artifacts generated with conventional methods. The photon counting detectors offer substantial improvements because of their ability to detect single events and the decrease of leakage current effects. This is why this research is based on the implementation of this technique to study these contrast improvements in various materials. To accomplish this goal, the Medipix3RX detector was used to acquire spectral images that were compared with simulations performed with the GAMOS software. The experimental results verified the energy dependence of the attenuation, showing monotonically decreasing changes with the increase of the energy threshold value, and were corroborated with the simulations. The results from the three studied phantoms successfully showed that the technique allows the differentiation among materials with high and low density differences, also allowing materials with the same geometry to be distinguished.